2017
DOI: 10.1021/acs.est.7b04417
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Health Effects from Molecular to Global Scales

Abstract: Poor air quality is globally the largest environmental health risk. Epidemiological studies have uncovered clear relationships of gaseous pollutants and particulate matter (PM) with adverse health outcomes, including mortality by cardiovascular and respiratory diseases. Studies of health impacts by aerosols are highly multidisciplinary with a broad range of scales in space and time. We assess recent advances and future challenges regarding aerosol effects on health from molecular to global scales through epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
355
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(392 citation statements)
references
References 380 publications
(551 reference statements)
8
355
0
Order By: Relevance
“…We compared the observed DTT activities to results described in reports of earlier studies. The respective DTT m of fine and coarse particles reported at urban background sites are typically 20–80 and 10–20 pmol min −1 μg −1 (Shiraiwa et al, ). For both size fractions, DTT m observed in this study were within the ranges that have been typically described in reports of earlier studies.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the observed DTT activities to results described in reports of earlier studies. The respective DTT m of fine and coarse particles reported at urban background sites are typically 20–80 and 10–20 pmol min −1 μg −1 (Shiraiwa et al, ). For both size fractions, DTT m observed in this study were within the ranges that have been typically described in reports of earlier studies.…”
Section: Resultsmentioning
confidence: 99%
“…The fuels in lab experiments, however, may be well aged and dried and thus have a much lower moisture content than fuels in the field, and the wind conditions in the field are impossible to reproduce in the lab. This can be seen in the values of the modified combustion efficiency (MCE; the ratio of CO 2 /( CO 2 + CO)) in many lab studies, which are much higher than those typical of field burns, an extreme example being the study by Sirithian et al (2018), who reported a mean MCE of 0.9996 in a lab study on biofuel burning. Therefore, lab results are only used in some special cases, where little or no field data are available, and where the lab data appear representative based on their MCE (e.g., Christian et al, 2003) or had been adjusted to reflect field conditions using "overlap species", emission ratios (ERs), or MCE as discussed in Yokelson et al (2013b).…”
Section: Data Selectionmentioning
confidence: 99%
“…These gaseous pollutants, and even more so the particulate matter from biomass burning, pose grave risks to human health (Naeher et al, 2007;Akagi et al, 2014;Dennekamp et al, 2015;Knorr et al, 2017;Apte et al, 2018). Recent estimates of global excess mortality from outdoor air pollution range from 4.2 to 8.9 million annually (Cohen et al, 2017;Lelieveld and Pöschl, 2017;Shiraiwa et al, 2017;Burnett et al, 2018;Lelieveld et al, 2019), with smoke from open vegetation burning accounting for up to 600 000 premature deaths per year globally (75th percentile of model estimates; Johnston et al, 2012). In addition to outdoor exposure, pollution from indoor solid fuel use, much of it biofuel burning, has been estimated to cause 2.8 million premature deaths annually (Kodros et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many other applications of aerobiology followed within the first half of the twentieth century, including population biology, aero-allergology, and the detection of biowarfare agents (Gregory 1961;Stackman et al 1942). Today, research regarding the sources, properties, concentrations, and diversity of bioaerosol is motivated by increasingly diverse questions and needs (e.g., Burge 1990;Cox and Wathes 1995;Cox et al 2019;D'Amato et al 2007;Fr€ ohlich-Nowoisky et al 2016;Morris et al 2014a;N uñez et al 2016;Santl-Temkiv et al 2019;Shiraiwa et al 2017;Sorensen et al 2019;Womack, Bohannan, and Green 2010). Many applications use the same broad principles of detection, however.…”
Section: Introductionmentioning
confidence: 99%